Evolution of disaster nursing research in the past 30 years (1990–2019): A bibliometric and mapping analysis. (May 2021) - Molassiotis, Alex; Guo, Chunlan; Abu-Odah, Hammoda; West, Caryn; Loke, Alice Yuen
Abstract: Background: Despite the development in disaster nursing and the increasing research and related publications, little efforts have been directed to map the global development and trends of disaster nursing literature, identify gaps and guide future research directions in the field. Objectives: To generate a comprehensive picture of publications in disaster nursing over the past three decades and provide a discussion on the gaps and directions for future developments in disaster nursing-related research. Methods: A bibliometric analysis was used. The Scopus database was utilized to retrieve disaster nursing publications for the period from 1990 to 2019. Findings: A total of 1075 publications on disaster nursing were retrieved. The analysis indicated a rapid growth in publications from 2001 to 2014, followed by a plateau. Disaster nursing publications were geographically polarized within the Anglo-Saxon, European Union and Asian countries, with the United States, Australia, and the United Kingdom being the top three most productive countries. Both the number of publications by year and countries were significantly correlated with the number of total damages caused by disasters (r = 0.42, p < 0.05 and r = 0.41, p < 0.001 respectively). The analysis also highlighted that most of the impactful cooperation among different authors was found within the same countries only. The main keyword-based themes of the publications included disaster, nurses/emergency nurses/military nurses, preparedness, communication, and knowledge. The disaster phase of response received the most attention in disaster nursing followed by preparedness, while very few publications addressed disaster mitigation and recovery . Conclusions: This study provides nursing leaders, educators, researchers, and practitioners a comprehensive map of the development of disaster nursing literature in the past three decades. However, the field of disaster nursing is still far from being mature. More empirical and theoretical research, especially in the full spectrum of disaster management, should be investigated to meet the global challenge of disasters. International collaboration should be a significant way in improving the quality of the related research.